Pengaruh Viral Marketing Shopee Affiliate, Kualitas Produk, dan Harga Terhadap Minat Beli Konsumen Shopee - Rolando, Benediktus; Nur Azizah, Fitrica; Karaniya Wigayha, Carmel (Forum Kerjasama Pendidikan Tinggi, 2024)
This study aims to examine the influence of viral marketing, product quality, and price on consumer purchase intention on the Shopee e-commerce platform. Data were collected through a questionnaire-based survey involving 100 university students in the Tangerang area, using a purposive sampling approach. The data were analyzed using multiple linear regression analysis, with validity, reliability, and classical assumption testing conducted via SPSS version 26 statistical software. The results indicate that all three independent variables have positive and significant effects on consumer purchase intention, with viral marketing (t-count=6.854, p=0.0394), product quality (t-count=5.994, p=0.001), and price (t-count=6.840, p=0.000) each exceeding the t-tabel value (1.650). The F-test (F=8.932 > F-tabel=2.28) confirms the simultaneous influence of these three variables. Theoretically, this study enriches the existing literature on consumer behavior by providing empirical evidence that supports marketing theories emphasizing the importance of digital strategies, product attributes, and pricing in shaping consumer choices, particularly in the e-commerce sector. From an industry perspective, the findings highlight the critical role of viral marketing in boosting consumer purchase intention and purchase decisions, suggesting that e-commerce platforms like Shopee should continue investing in digital marketing campaigns and influencer collaborations. Additionally, the study demonstrates that maintaining high product quality and offering competitive prices are key to driving purchase decisions, providing valuable strategic insights for businesses to refine their marketing, product management, and pricing strategies.